DALE’S THEORY DAN BRUNER’S THEORY (ANALISIS MEDIA DALAM PENTAS WAYANG SANTRI KI ENTHUS SUSMONO) - Muhammad Nasurllah, Hamdan Adib, Syafrawi, M. Sahibudin, (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2021)
Abstract The development of the media begins with the scientific construct of media by Edgar Dale who provides a very valuable contribution to science, namely the linkage between media and learning experiences, assisted by Jerome S Bruner's theory which divides experience into three namely active, pictorial and symbolic, and provides the basis for The use of theory starts from the most abstract things to the most concrete things and is formulated in the cone of Edgar Dale's experience. This study aims to analyze the wayang santri performances performed by Ki Enthus Susmono using the theory of Edgar Dale and Jermoe s Bruner. This research is a type of library research research and the data analysis used is content analysis. Media innovation was carried out by a puppeteer from Tegal, namely Ki Enthus Susmono by making a new breakthrough in wayang, namely wayang santri which was intended to educate the public about the teachings of Islam. The da'wah media used in the wayang santri is the wayang golek media which has been modified with various Islamic icons to the sinden and the stories in it. The media used by Ki Enthus when looking at Edgar Dale's theory enters the visual level and enters the pictoral level on Bruner's theory, both of which show that learning uses media in the form of images or other visual forms that help people understand Islamic teachings brought by Ki Enthus. The method used by Ki Enthus is the lecture method.